2021
DOI: 10.1101/2021.02.22.21252026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mass balance model perfectly fits both Hall et al. underfeeding data and Horton et al. overfeeding data

Abstract: Background & Aims Recently, the validity of mass balance model (MBM) was questioned based on two feeding studies. Thus, we simulated both of these feeding trials. Methods MBM describes the temporal evolution of body weight and body composition under a wide variety of feeding experiments. This computational study simulated, utilizing MBM, the underfeeding trial by Hall et al. (Cell Metab. 2015;22:427-36) and the overfeeding trial by Horton et al. (Am J Clin Nutr. 1995;62:19-29). Results Our simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 4 publications
3
12
0
Order By: Relevance
“…B1. Fat loss trajectories that underlay weight loss in A1 perfectly match those reported by Hall et al [3] over the trial duration (6 days). B2.…”
Section: Simulation According To the Mass Balance Model (Mbm)supporting
confidence: 83%
See 1 more Smart Citation
“…B1. Fat loss trajectories that underlay weight loss in A1 perfectly match those reported by Hall et al [3] over the trial duration (6 days). B2.…”
Section: Simulation According To the Mass Balance Model (Mbm)supporting
confidence: 83%
“…A growing body of evidence indicate that the widely accepted EBT ("Calories In, Calories Out) is a flawed paradigm. Instead, it is becoming increasingly clear that body mass is regulated according to the "Mass In, Mass Out" principle [2,3,4,5,6,9]. A very comprehensive and detailed review can be found in source [9], while a relatively easy-to-read and practical review can be found in [5].…”
Section: Simulation According To the Mass Balance Model (Mbm)mentioning
confidence: 99%
“…For further details, please see, including Supplementary Files, [1], [2] and [3]. Please note that only the most important references are listed for this article, as the others can be found in the aforementioned papers.…”
Section: Discussionmentioning
confidence: 99%
“…A highly significant practical application of a mass balance approach is that a low-carbohydrate/high-fat diet leads to a greater body mass and fat mass loss than an isocaloric high-carbohydrate/low-fat diet because it provides less nutrient mass [1,2,3]. When the energy fraction from dietary fat increases, while energy intake is clamped (i.e., fixed), mass intake decreases due to the significantly higher energy density of fat compared with other energy substrates.…”
Section: A Low-carbohydrate Diet Vs An Isocaloric High-carbohydrate Dietmentioning
confidence: 99%
See 1 more Smart Citation